Countering Islamophobia in Europe - Law, Ian.; Easat-Daas, Amina; Merali, Arzu.; Sayyid, S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The treatment of Muslims is the touchstone of contemporary European racism across its many nations and localities. We make a definitive case for two arguments in this book: firstly, the recognition of the accelerating and pervasive nature of Islamophobia in this region; and secondly, recognition that this process is being, can be, and will be challenged by counter-narratives that make the claim for Muslim humanity, plurality, space and justice. This book draws on new evidence from eight national contexts to provide an innovative kit of counter-narratives, which were presented and well received at the European Parliament in September 2018, and subsequently launched across Europe in national workshops in selected states. A synergy between leading academic researchers and the Islamic Human Rights Commission, Countering Islamophobia in Europe will be of value to EU institutions, governments and policy-makers, NGOs and media organisations, as wellas researchers of multiculturalism, Islam, Muslims and immigration.
1. Introduction; Ian Law, S. Sayyid, Arzu Merali & Amina Easat-Daas -- 2. Islamophobia as a Key Contextual Factor in Human Rights Adjudication; Ilias Tripolitis -- 3. Countering Islamophobia in the UK; Arzu Merali -- 4. Countering Islamophobia in Greece; Matilda Chatzipanagiotou & Iason Zarikos -- 5. Countering Islamophobia in Hungary; Zsuzsanna Vidra -- 6. Countering Islamophobia in the Czech Republic; Karel Čada &Veronika Frantová -- 7. Countering Islamophobia in Portugal; Marta Araújo, Silvia Rodríguez Maeseo & Max Ruben Ramos -- 8. Countering Islamophobia in France; Andrea Bila -- 9. Countering Islamophobia in Belgium; Elsa Mescoli -- 10. Countering Islamophobia in Germany; Luis Manuel Hernández Aguilar -- 11. A New Counter-Islamophobia Kit; Ian Law, S. Sayyid & Amina Easat-Daas.
Keywords: Political sociology; Critical criminology; Race; Islam; Political Sociology; Critical Criminology; Race and Ethnicity Studies; Islam